Gut microbiota dysbiosis in ankylosing spondylitis: a systematic review and meta-analysis - Su, Qin-Yi; Zhang, Yan; Qiao, Dan; Song, Xia; Shi, Yang; Wang, Zhe; Wang, Chen-Yan; Zhang, Sheng-Xiao (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAnkylosing spondylitis (AS) is a connective tissue disease that primarily affects spinal joints, peripheral joints, and paravertebral soft tissues, leading to joint stiffness and spinal deformity. Growing evidence has implicated gut microbiota in the regulation of AS, though the underlying mechanisms remain poorly understood.MethodsWe conducted a comprehensive search of PubMed, Embase, Web of Science, the Cochrane Library, MEDLINE, Wanfang Data, China Science and Technology Journal Database (VIP), and China National Knowledge Internet (CNKI) databases from the time the databases were created until 30 July 2023. To evaluate changes in α-diversity and the abundance of certain microbiota families in AS, standardized mean difference (SMD) and 95% confidence interval (CI) calculations were made. Meta-analyses were performed using STATA 12.0 and the quality of the literature was assessed by following systematic review guidelines.ResultsThis systematic review and meta-analysis included 47 studies, providing insights into the gut microbiota composition in patients with AS compared to healthy controls (HCs). Our findings indicate a significant reduction in gut microbial diversity in patients with AS, as evidenced by a decrease in both richness and evenness. Specifically, the Shannon index showed a moderate decrease (SMD = -0.27, 95% CI: -0.49, -0.04; P < 0.001), suggesting a less diverse microbial ecosystem in patients with AS. The Chao1 index further confirmed this trend, with a larger effect size (SMD = -0.44, 95% CI: -0.80, -0.07; P < 0.001), indicating a lower species richness. The Simpson index also reflected a significant reduction in evenness (SMD = -0.30, 95% CI: -0.53, -0.06; P < 0.001). Additionally, patients with AS who received anti-rheumatic combination treatment exhibited a more pronounced reduction in α-diversity compared to untreated patients, highlighting the potential impact of this treatment on gut microbiota balance. In terms of specific microbial families, we observed a significant decrease in the abundance of Bifidobacterium (SMD = -0.42, 95% CI: -2.37, 1.52; P < 0.001), which is known for its beneficial effects on gut health. Conversely, an increase in the abundance of Bacteroidetes was noted (SMD = 0.42, 95% CI: -0.93, 1.76; P < 0.001), suggesting a possible shift in the gut microbiota composition that may be associated with AS pathophysiology.ConclusionOur analysis revealed changes in α-diversity and the relative abundance of specific bacteria in AS. This suggests that targeting the gut microbiota could provide new therapeutic opportunities for treating AS.Systematic review registrationhttps://www.crd.york.ac.uk./PROSPERO/, identifier CRD42023450028.